Almanaques de São Carlos (SP), um caleidoscópio de imagens da cidade (1894-1928) - Fonseca, Arrovani Luiz (2019)
The study analyzes the almanacs of the city of São Carlos, countryside of São Paulo, published in 1894, 1905, 1915, 1916-17, 1927 and 1928 within the context of coffee expansion. The historical period involved, which we call Belle Époque Caipira, considers the economic and political rise of the elites in the cities of the countryside of São Paulo, conducting the actions of the process of urban modernization under the discourse of civilization and progress. In this sense, the almanac, a traditional publication of diverse contents with a great presence in the Brazilian written culture, is perceived here as printed papers organized by its editors as bearers of discourses referring to the modern. It was thus for us to enter its pages analyzing literature, advertisements, historical texts, photographic images, to observe the pluralized perception of the process of modernization. Thus, the metaphor of the kaleidoscope of images of the urban makes sense when we come to understand its profile of representation of the city. The research is based on the discussions around the concepts of modernity / modernization / modern, progress and civilization, allowing a construction of aspects of the transformations of the city of São Carlos. We still need to go through a history of the origin of the almanacs up to the end of the 19th century and the beginning of the first decades of the 20th century to visualize the permanences and changes existing in this editorial genre, bringing them closer to those of São Carlos. We deal with the almanacs in this study as a source and object of research showing its historicity in relation to other printed matter of the period in question